International Trade in the Age of Turbulent Uncertainty, Globalization, Regionalization and Pandemic - Evdokimov, Alexander Ivanovich; Guliyev, Mushfig Yelmar (International Journal of Criminology and Sociology, 2022)
Purpose: This paper analyzes the modern aspects of the international trade policy system in the context of the active development of integration processes in various regions, assesses the role of the WTO (The World Trade Organization) and some ways to improve its activities in accordance with modern challenges. Methods: The methods of comparison, synthesis, abstraction, and modeling based on available information and analytical resources were used. Results: The draft of the future international trade order, especially if it is based on a network of related regional and interregional trade agreements, can become increasingly practical for the effectiveness of trade relations and public confidence regarding the idea of ​​openness and globalization. Conclusion: The main idea of this study is that the global regulation of international trade and the influence of turbulent currents of uncertainties at the national level can be improved with a higher degree of sustainable win-win approaches to reforming the WTO and regional spaces of trade relations.